INTEGRATING ECONOMIC, ENVIRONMENTAL, AND TRADE DETERMINANTS OF ELECTRIC VEHICLE IMPORTS IN ASEAN - Ni Ketut Budiningsih; Ni Putu Wiwin Setyari; Yustirania Septiani; Clara Elisabeth Jahja Saputra; Ni Made Ayu Diah Gayatri Pitaloka (Media Ekonomi, 2026)
This study aims to examine the key economic, environmental, and trade policy factors influencing EV imports across ASEAN countries. Using panel data analysis with a fixed-effects approach, the study controls for unobserved country-specific characteristics while incorporating macroeconomic conditions, urbanization, environmental indicators, and trade policy variables. The findings indicate that market size and urban development consistently support higher EV imports, reflecting greater market readiness and demand potential for electric mobility. Exchange rate dynamics exhibit a diminishing influence once additional controls are introduced, suggesting that structural factors play a more dominant role in shaping EV trade patterns. Environmental pressures are positively associated with EV imports, suggesting that sustainability considerations contribute to a gradual shift toward cleaner transportation technologies. However, restrictive trade policies continue to limit the scale of EV imports across countries. These results highlight the importance of coherent trade, environmental, and infrastructure-related policies in facilitating EV market development. The study provides policy-relevant insights for governments seeking to accelerate EV diffusion through improved urban readiness, supportive economic conditions, and balanced trade regulations.